2008
DOI: 10.2166/wst.2008.529
|View full text |Cite
|
Sign up to set email alerts
|

Effects of electric polarization of indium tin oxide (ITO) and polypyrrole on biofilm formation

Abstract: The influence of electric polarization on primary adhesion and on biofilm formation was investigated. As substrata, indium tin oxide (ITO) and polypyrrole coatings were used because of their electric conductivity. The materials were polarized from -600 mV to +600 mV, switching every 60 seconds. Control was non-polarized substrata. Primary adhesion under this regime was not strongly influenced, however, the morphology of the primary biofilm was obviously different from that of the control. Biofilm formation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 16 publications
1
13
0
Order By: Relevance
“…By controlling the surface physical–chemical properties, bacterial and cell adhesion can be controlled. Controlling bacterial adhesion to the PPy surface has been achieved by different strategies like coating the surface with specific types of protein or applying a direct or pulsed electric current or potential through the film . We have previously shown that the adhesion also depends on the dopant and redox state of PPy .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…By controlling the surface physical–chemical properties, bacterial and cell adhesion can be controlled. Controlling bacterial adhesion to the PPy surface has been achieved by different strategies like coating the surface with specific types of protein or applying a direct or pulsed electric current or potential through the film . We have previously shown that the adhesion also depends on the dopant and redox state of PPy .…”
Section: Resultsmentioning
confidence: 99%
“…Controlling bacterial adhesion to the PPy surface has been achieved by different strategies like coating the surface with specifi c types of protein [ 28 ] or applying a direct or pulsed electric current or potential through the fi lm. [ 29,30 ] We have previously shown that the adhesion also depends on the dopant and redox state of PPy. [ 24 ] In order to investigate the effect of the surface physical-chemical properties of PPy on bacterial adhesion, we have chosen a set of four PPy surfaces from the previous 25 different variants that either have similar roughness with different contact angles, or similar contact angles with different roughness.…”
Section: Bacterial Adhesion On the Polymersmentioning
confidence: 99%
“…Electrolytic cleaning of metal surfaces is a well-established technique in many industrial applications , and it has recently been used to remove biofilm or prevent its formation. The electrochemical polarization of metallic surfaces destabilizes and breaks adhering biomolecules and organisms leading to their detachment from the metallic surfaces . It also causes local change in pH and generates active oxidants and reducing agents, such as oxygen, hydroxide ions, and protons that are able to inactivate or reduce the number of viable microorganisms. ,, Another advantage of the electrochemical treatment is that it can access different surfaces with difficult topographies.…”
Section: Introductionmentioning
confidence: 99%
“…Already in 1971, Marshall et al tried to understand microbial primary adhesion as the interaction between "living colloids" and surfaces, applying the theory of Derjaguin, Landau, Vervey, and Overbeck (DLVO), a concept which was further evaluated for a long time (Hermansson 2000), but it clearly did not allow for realistic predictions as recent research confirmed (Schaule et al 2008). Obviously, this approach does not acknowledge all factors involved in primary adhesion, in particularly not the role of EPS, or cellular appendices.…”
Section: Low-fouling Surfacesmentioning
confidence: 99%
“…This is also in its early experimental development but may open an interesting window in mitigation of biofouling. Schaule et al (2008) used surfaces coated with indiumtinoxide (ITO) and polarized them at AE600 mV under potentiostatic conditions in a pulsing routine of 1 min. Originally, this approach was intended to prevent microbial adhesion but failed to do so.…”
Section: Low-fouling Surfacesmentioning
confidence: 99%